2005
DOI: 10.1074/jbc.m507532200
|View full text |Cite
|
Sign up to set email alerts
|

The Conformation of a Signal Peptide Bound by Escherichia coli Preprotein Translocase SecA

Abstract: To understand the structural nature of signal sequence recognition by the preprotein translocase SecA, we have characterized the interactions of a signal peptide corresponding to a LamB signal sequence (modified to enhance aqueous solubility) with SecA by NMR methods. One-dimensional NMR studies showed that the signal peptide binds SecA with a moderately fast exchange rate (K d ϳ 10 ؊5 M). The line-broadening effects observed from one-dimensional and two-dimensional NMR spectra indicated that the binding mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…This possibility is considered unlikely for the following reasons: The TMS4c peptides have a net negative charge, whereas that of signal peptides is usually positive due to the characteristic positively charged residues in the N terminus. It has recently been shown that these positively charged residues are directly involved in signal sequence binding to SecA, 31 which is in marked contrast to the negatively charged residue (Glu176) that is the main determinant for binding of TMS4c to SecA. Furthermore, if the interaction with TMS4c would represent SecA binding to the mature region of a pre-protein, many more peptides are expected to bind SecA.…”
Section: Discussionmentioning
confidence: 89%
“…This possibility is considered unlikely for the following reasons: The TMS4c peptides have a net negative charge, whereas that of signal peptides is usually positive due to the characteristic positively charged residues in the N terminus. It has recently been shown that these positively charged residues are directly involved in signal sequence binding to SecA, 31 which is in marked contrast to the negatively charged residue (Glu176) that is the main determinant for binding of TMS4c to SecA. Furthermore, if the interaction with TMS4c would represent SecA binding to the mature region of a pre-protein, many more peptides are expected to bind SecA.…”
Section: Discussionmentioning
confidence: 89%
“…The crystal structure of the monomeric form of Bacillus subtilis SecA revealed an open groove similar to the substrate-binding grooves of molecular chaperones (10). In addition, SecA has another and shallower groove located more closely to NFB1 and HSD (6, 10) with possible complementarity to a signal peptide (35). It is conceivable that such substrate-binding cavities are used for the second mode of preprotein binding used for the actual movement of the preprotein.…”
Section: Discussionmentioning
confidence: 99%
“…92 The observed trNOEs showed that the bound signal peptide adopts an a-helical structure in the h-and c-regions, and differential line broadening argued that one side of the helix in the h-region is more strongly bound to SecA ( Figure 5). Additionally, the positive n-region and the hydrophobic h-region of the signal peptide were intimately involved in binding.…”
Section: Seca-signal Sequence Recognitionmentioning
confidence: 98%